Rethinking risk management practices in light of the Icelandic financial crisis - Stárek, Václav (2012)
Foremost, the thesis aims at mapping and analysing several aspects of the Icelandic financial crisis relevant to the practice of risk management, particularly with respect to banking sector. It identifies six possible sources of vulnerability occurring in the pre-crisis period. The domestic banking sector along with the entire Iceland's economy was pressurised by these stressors, which gradually led to the meltdown. The second chapter opens a discussion about the nature and characteristics of uncertainty and risk. It further strives to classify both the degrees of uncertainty and the elements of business and financial risks. The final chapter probes into the trickiness of dependence and expectations (in statistical sense of these terms), especially examining the limitations imposed on linear correlation as well as the violation of the assumptions underlying historical Value-at-risk and Expected shortfall approaches to estimating market risk.